In vitro and in vivo pharmacokinetic characterization of mavacamten, a first-in-class small molecule allosteric modulator of beta cardiac myosin. (3rd June 2019) - Grillo, Mark P.; Erve, John C. L.; Dick, Ryan; Driscoll, James P.; Haste, Nicole; Markova, Svetlana; Brun, Priscilla; Carlson, Timothy J.; Evanchik, Marc
Abstract: Mavacamten is a small molecule modulator of cardiac myosin designed as an orally administered drug for the treatment of patients with hypertrophic cardiomyopathy. The current study objectives were to assess the preclinical pharmacokinetics of mavacamten for the prediction of human dosing and to establish the potential need for clinical pharmacokinetic studies characterizing drug–drug interaction potential. Mavacamten does not inhibit CYP enzymes, but at high concentrations relative to anticipated therapeutic concentrations induces CYP2B6 and CYP3A4 enzymes in vitro . Mavacamten showed high permeability and low efflux transport across Caco-2 cell membranes. In human hepatocytes, mavacamten was not a substrate for drug transporters OATP, OCT and NTCP. Mavacamten was determined to have minimal drug–drug interaction risk. In vitro mavacamten metabolite profiles included phase I- and phase II-mediated metabolism cross-species. Major pathways included aromatic hydroxylation (M1), aliphatic hydroxylation (M2); N -dealkylation (M6), and glucuronidation of the M1-metabolite (M4). Reaction phenotyping revealed CYPs 2C19 and 3A4/3A5 predominating. Mavacamten demonstrated low clearance, high volume of distribution, long terminal elimination half-life and excellent oral bioavailability cross-species. Simple four-species allometric scaling led to predicted plasma clearance, volume of distribution and half-life of 0.51 mL/min/kg, 9.5 L/kg and 9 days, respectively, in human.